Economic growth drivers and foreign direct investment in ASEAN-5 countries: Short-term and long-term impacts - Nguyen, Yen Hai; Pham, Luu Ngoc Khanh (Asian Journal of Economic Modelling, 2025)
This study investigates the impact of foreign direct investment (FDI) on economic growth in five ASEAN countries: Vietnam, Thailand, Indonesia, Malaysia, and the Philippines, over the period 1990–2021. Using the Pooled Mean Group-Autoregressive Distributed Lag (PMG-ARDL) model, the research analyzes both long-run and short-run dynamics among key macroeconomic variables, including FDI, physical capital, labor, and trade openness. The empirical findings confirm a significant long-run relationship in which increases in all four variables positively contribute to economic growth. In the short run, only FDI, capital, and labor exhibit a statistically significant positive effect. Results from Granger causality tests indicate that GDP plays a central role in attracting FDI, promoting trade openness, and driving capital accumulation. The analysis also uncovers bidirectional causality between FDI and trade openness, as well as between capital and labor. These findings highlight the vital contribution of FDI to long-term economic development in ASEAN-5 countries, while also emphasizing the importance of maintaining balanced growth across complementary economic drivers. Policymakers are therefore advised to avoid overdependence on FDI inflows and instead adopt integrated strategies aimed at ensuring macroeconomic stability, enhancing domestic investment, and improving labor productivity. A coordinated policy framework that harmonizes efforts across FDI, trade, capital, and labor will be key to fostering sustained and inclusive growth in the region.